PKM DOSEN PENERAPAN STRATEGI MARKETING MELALUI ANALISIS DATA PENJUALAN UMKM DI DKI JAKARTA - Jubaedah, Jubaedah; Desmintari, Desmintari; Setiadi, Iwan Kresna; Manggabarani, Alfatih Sikki; Wikantari, Maria Assumpta; Praptiningsih, Praptiningsih (Batara Wisnu : Indonesian Journal of Community Services, 2023)
This community service program is a collaboration between a team of lecturers from UPN Veteran Jakarta and Micro, Small and Medium Enterprises (MSMEs) in DKI Jakarta. This activity is useful between UPN Veteran Jakarta and MSMEs Level Up Kominfo RI. This program is not only a form of cooperation between educational institutions and government institutions, but also as a form of community service from UPNVJ lecturers through the implementation of the tridharma of higher education. With a focus on developing marketing strategies, this activity aims to help MSMEs utilize sales data to improve their marketing performance. The lecturer team collaborates with MSMEs in collecting, analyzing, and interpreting sales data to identify relevant patterns and trends in consumer behavior. Based on these findings, a marketing strategy was developed tailored to the characteristics of the local market and consumer needs. The strategy includes the utilization of social media, online platforms, proper market segmentation, and appropriate product development. In addition, this program also involves training activities and workshops to improve understanding and marketing skills for MSMEs. Through this collaboration, it is hoped that MSMEs in DKI Jakarta can strengthen their position in the market and increase their competitiveness in a sustainable manner. This program is a concrete step in supporting local economic growth and the development of MSMEs as an important pillar in the economy. After the service activities, MSMEs in DKI Jakarta benefit from more effective marketing strategies, increased sales, and a better understanding of using sales data. This has an impact on local economic growth and the empowerment of MSME communities